Low levels of vitamin D in neuromyelitis optica spectrum disorder: association with disease disability. - Ju-Hong Min (Public Library of Science (PLoS), 2014)
Patients with autoimmune disorders often have low levels of 25-hydroxyvitamin D [25(OH)D3], which correlates with disability or disease activity. Vitamin D may play a role in neuromyelitis optica (NMO) or NMO spectrum disorder (NMOSD), as an important factor involved in immunological pathways. We investigated the relationship between vitamin D levels and disease related disability and clinical activity in patients with NMOSD. Blood samples from 51 patients with NMOSD who were positive for anti-aquaporin4-antibody (AQP4-ab) and 204 healthy controls were collected for 25(OH)D3 measurement. Clinical parameters, including expanded disability status scale (EDSS) score, annualized relapse rate (ARR) and time of blood sampling relative to attack, were determined in patients with NMOSD. We found that 25(OH)D3 levels were significantly lower in patients with NMOSD compared to healthy controls. There was no difference between 25(OH)D3 levels in blood samples taken at relapse or remission, and no association between 25(OH)D3 levels and ARR, but there was an inverse correlation between 25(OH)D3 levels and EDSS scores in patients with NMOSD. It remains to be determined whether low vitamin D levels predispose to NMO and/or modify disease severity, or are secondary to neurological disability. In either case the results could also be of relevance to other neurological diseases such as multiple sclerosis as well as NMO.